Proarrhythmic effects of domperidone in infants: a systematic review - Marta Marzi; Lucía Caraballo; Gabriel Molina; Darío Weitz; Laura Piskulic; Aylén Avila (Elsevier, 2014)
Aims: To assess the association of the use of domperidone in infants with QTc interval prolongation and proarrhythmic events. Methods: A systematic search of the scientific literature was conducted without any date or language restriction. The electronic database MEDLINE and the sources LILACS, ScIELO and Cochrane library were consulted. Results: From the twelve identified studies, eight were excluded because they did not meet the inclusion criteria. One case report and three pilot studies were selected. Rocha et al (2005) reported the case of an infant (age 3 months) with QTc interval = 463 ms after being treated during one month with 1.8 mg/kg/day of oral domperidone. Djeddi et al (2008) administered an average dose of 1.3 mg/kg/day to 31 neonates; QTc interval prolongation > 30 ms was observed in nine neonates. Hegar et al (2009) studied 10 infants (mean age 5.6 months) who received 0.8 mg/ kg/day of oral domperidone; QTc interval prolongation was not observed. Günlemez et al (2010) enrolled 40 premature infants who were administered 1 mg/kg/day of oral domperidone; the QTc interval increased to above 450 ms in two infants. Conclusions: Although evidence that orally administrated domperidone in infants produces prolongation of QTc interval was found, further studies are needed in order to quantify the risk associated with the drug in that population. We suggest that heath professionals should conduct ECGs to infants treated with domperidone and inform the pharmacovigilance system the occurrence of any case of adverse event